PENGARUH PENDAPATAN USAHA PRODUKTIF ISTRI NELAYAN TERHADAP PENDAPATAN KELUARGA NELAYAN DI KECAMATAN BANGGAE KABUPATEN MAJENE - zulkifli zulkifli (Eqien - Jurnal Ekonomi dan Bisnis, 2020)
The purpose of this study was to study the productive income of fishermen towards the income of fishermen families in Banggae District, Majene Regency. The data analysis technique used in this study is a simple linear regression test.research results results of management of factors that may be obtained by many positives and high functions for spending women's families in bangung sub-district, majene regencyThe purpose of this study was to study the productive income of fishermen towards the income of fishermen families in Banggae District, Majene Regency. The data analysis technique used in this study is a simple linear regression test.research results results of management of factors that may be obtained by many positives and high functions for spending women's families in bangung sub-district, majene regency